HIV SCREENING TEST IN A NEWLY DIAGNOSED TB PATIENT: A CASE STUDY - Ira Rahmawati; Sumirah Budi Pertami (Alta Dharma Publisher, 2019)
Human immunodeficiency virus (HIV) is the most significant risk factor for having tuberculosis (TB) diseases as people with HIV are 20 times more likely to develop TB disease compared to non-HIV individuals. This paper discusses the case of Lucas (pseudonym), who presented to the emergency department (ED) with history of chronic diarrhoea and symptoms suggesting TB diseases. Lucas was then found to have an active TB infection and According to the guidance on provider-initiated HIV testing and counselling in health facilities, HIV screening should performed or offered to newly diagnosed TB patients. However, Lucas was not offered to do HIV testing, which may possibly cause inadequate TB therapy that he received. This paper further discusses the pathophysiology of HIV and TB coinfection, followed by a discussion of the nursing assessment and management as well as the medical management in the ED. Then, HIV related stigma will be discussed, as it can be a barrier for introducing HIV testing in TB patients.